Chelon labrosus ... - Bariche, Michel; Fricke, Ronald (Zenodo, 2020)
Chelon labrosus (Risso 1827) —Thicklip grey mullet Taxonomy. First record from Lebanon as Mugil chelo, Cuv. by Gruvel (1931: 88); subsequently recorded as Mugil chelo Cuvier 1829 by George et al. (1964: 16); as Chelon labrosus Risso by Mouneimné (1977: 65); as Chelon labrosus (Risso 1826) by Mouneimné (2002: 185–186); recently recorded as Chelon labrosus by Bariche et al. (2009: 3). Material in collection: AUBM. Distribution. Baltic Sea, North Sea, Mediterranean Sea, Sea of Marmara, Black Sea, eastern Atlantic: Norway and Iceland south to Senegal, including Azores, Madeira, Canary Islands and Cape Verde Islands. Conservation. IUCN: Global (LC: 1 January 2008); Med. (LC: 16 November 2007). Capture and threats: FIT, FIB, unknown. Occurrence: Common. Low priority for conservation action. ... : Published as part of Bariche, Michel & Fricke, Ronald, 2020, The marine ichthyofauna of Lebanon: an annotated checklist, history, biogeography, and conservation status, pp. 1-157 in Zootaxa 4775 (1) on page 50, DOI: 10.11646/zootaxa.4775.1.1, http://zenodo.org/record/3983887 ...